2006
DOI: 10.7326/0003-4819-145-4-200608150-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nurse Management on the Quality of Heart Failure Care in Minority Communities

Abstract: Nurse management can improve functioning and modestly lower hospitalizations in ethnically diverse ambulatory care patients who have heart failure with systolic dysfunction. Sustaining improved functioning may require continuing nurse contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 38 publications
3
119
0
8
Order By: Relevance
“…[11][12][13][14] However, the barriers and facilitators of task redistribution of hypertension care from physicians to nurses in rural LMIC settings are not known. We therefore conducted a qualitative study to evaluate the specific factors influencing nurse management of hypertension in rural western Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] However, the barriers and facilitators of task redistribution of hypertension care from physicians to nurses in rural LMIC settings are not known. We therefore conducted a qualitative study to evaluate the specific factors influencing nurse management of hypertension in rural western Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the difficulty HF imposes in the everyday life of the elderly, reflect on their HRQOL and it has been demonstrated that elderly with HF presented high scores in all dimensions of the LHFQ, that is worse HRQOL compared to healthy individuals (7) . Additionally, it is important to implement strategies to improve HRQOL, because poor quality of life is associated with clinical worsening, including the increase in hospital admission and mortality rate (27) . An important remark refers to the increase of LHFQ scores connected with HF severity.…”
Section: Discussionmentioning
confidence: 99%
“…82,88 An intervention designed to improve problem-solving skills in patient and family dyads showed a positive effect on change in perceived control. 60 TPE interventions using direct 1-to-1 interactions did not reduce all-cause or cardiac mortality, 68,76,87,91 with the exception of a study by Dracup and colleagues 72 ; however, more studies showed a benefit of 1-to-1 TPE interventions Better attitude about dietary sodium intake at 6 wk (P=0.01)…”
Section: Hf Outcomesmentioning
confidence: 99%
“…88 Other TPE interventions provided approaches that included feedback on dietary intake patterns and enhancing medication adherence. 63,73,74,87,92,94,95 The activation of selfmanagement resources (eg, environmental restructuring, eliciting support from family, cognitive restructuring, and relaxation response) 82 and the use of family-focused interventions were other strategies used in other self-management trials 60,73 to enhance mutual support, communication, and problem-solving skills…”
mentioning
confidence: 99%